A Framework for Using eHealth Interventions to Overcome Medical Mistrust Among Sexual Minority Men of Color Living with Chronic Conditions. Issue 2 (3rd April 2019) - Ramos, S. Raquel; Warren, Rueben; Shedlin, Michele; Melkus, Gail; Kershaw, Trace; Vorderstrasse, Allison
Abstract: The purpose of this paper is to present a stepwise, multi-construct, innovative framework that supports the use of eHealth technology to reach sexual minority populations of color to establish trustworthiness and build trust. The salience of eHealth interventions can be leveraged to minimize the existing paradigm of medical mistrust among sexual minority populations of color living with chronic illnesses. These interventions include virtual environments and avatar-led eHealth videos, which address psychosocial and structural-level challenges related to mistrust. Our proposed framework addresses how eHealth interventions enable technology adoption and usage, anonymity, co-presence, self-disclosure, and social support and establish trustworthiness and build trust.